Multifunctional Ti–Me (Me = Al, Cu) thin film systems for biomedical sensing devices. (December 2015) - Lopes, C.; Vieira, M.; Borges, J.; Fernandes, J.; Rodrigues, M.S.; Alves, E.; Barradas, N.P.; Apreutesei, M.; Steyer, P.; Tavares, C.J.; Cunha, L.; Vaz, F.
Abstract: Ti–Me binary intermetallic thin films based on a titanium matrix doped with increasing amounts of Me (Me = Al, Cu) were prepared by magnetron sputtering (under similar conditions), aiming their application in biomedical sensing devices. The differences observed on the composition and on the micro(structural) features of the films, attributed to changes in the discharge characteristics, were correlated with the electrical properties of the intermetallic systems (Ti–Al and Ti–Cu). For the same Me exposed areas placed on the Ti target (ranging from 0.25 cm 2 to 20 cm 2 ) the Cu content increased from 3.5 at.% to 71.7 at.% in the Ti–Cu system and the Al content, in Ti–Al films, ranged from 11 to 45 at.%. The structural characterization indicated the formation of metastable Ti–Me intermetallic phases for Al/Ti atomic ratios above 0.20 and for Cu/Ti ratios above 0.25. For lower Me concentrations, the effect of the α-Ti(Me) structure dominates the overall structure. With the increase in the amount of the Me into the Ti structure a clear trend for amorphization was observed. For both systems a significant decrease of the electrical resistivity with increasing Me/Ti atomic ratios (higher than 0.5 for Al/Ti atomic ratio and higher than 1.3 for Cu/Ti atomic ratio) was observed. Although similar trends were observed in the resistivity evolution for both systems, the Ti–Cu films presented lower resistivity values in comparison to the Ti–Al system. Highlights: Ti–Me (Me = Al, Cu) intermetallic thin films were deposited by magnetron sputtering. Ti matrix doped with different Me amounts was studied in terms of (micro)structural evolution. Structure and morphology was correlated with the electrical properties. Electrical conductivity improves with the formation of Ti–Me intermetallic phases, especially for higher Me contents. The films are suitable for biomedical sensing devices.